Landscape nucleating elements influence the zoochorous dispersion in upper-montane grasslands Elementos nucleadores da paisagem influenciam a dispersão zoocórica em áreas campestres alto-montanas - Dallabrida J.P.* (2017)
We aimed to determine the influence of nucleating elements on woody species regeneration, in three grassland areas, adjacent to fragments of Upper-montane Araucaria Forest. For this, three transects were allocated, one in each area, perpendicular to the fragments edges, with its extension covering the grassland area. All regenerative individuals of shrub-tree species greater than or equal to 20 cm height up to dbh < 5 cm were sampled and classified as zoochoric, anemochoric and autochoric. Adults individuals (dbh ≥ 5 cm), fallen stems, dead arborescent ferns, rocks were tested as nucleating elements. The spatial coordinates (x, y) of regenerative individuals and nucleating elements, soil physicochemical properties, soil compaction degree, and topography were obtained. The spatial dependencies between individuals of different dispersal guilds and nucleating elements were determined by O-rings statistics. The spatial relationships between individuals of distinct dispersal syndromes and nucleating elements differed among areas. Only individuals of zoochoric species presented association with nucleating elements, being the dead arborescent ferns, fallen stems and rocks the most effective elements. The different environmental conditions among areas resulted in distinct regeneration patterns and spatial relationship with nucleating elements.